Macrolide‐resistant Mycoplasma pneumoniae pneumonia in transplantation: Increasingly typical?. Issue 5 (19th May 2020) - Eschenauer, Gregory A.; Xiao, Li; Waites, Ken B.; Crabb, Donna M.; Ratliff, Amy E.; Gandhi, Tejal N.; Riddell, James; Kaul, Daniel R
Abstract: Mycoplasma pneumoniae is one of the most common bacterial causes of pneumonia. Macrolide‐resistant M pneumoniae (MRMP) was documented in 7.5% of isolates in the United States. Resistance portends poor outcomes to macrolide therapy, yet patients respond well to fluoroquinolones or tetracyclines such as minocycline. However, MRMP may be under‐appreciated because M pneumoniae generally causes relatively mild infections in non‐immunosuppressed adults that may resolve without effective therapy and because microbiological confirmation and susceptibility are not routinely performed. We report two cases of pneumonia due to MRMP in kidney transplant recipients. Both patients required hospital admission, worsened on macrolide therapy, and rapidly defervesced on doxycycline or levofloxacin. In one case, M pneumoniae was only identified by multiplex respiratory pathogen panel analysis of BAL fluid. Macrolide resistance was confirmed in both cases by real‐time PCR and point mutations associated with macrolide resistance were identified. M pneumoniae was isolated from both cases, and molecular genotyping revealed the same genotype. In conclusion, clinicians should be aware of the potential for macrolide resistance in M pneumoniae, and may consider non‐macrolide‐based therapy for confirmed or non‐responding infections in patients who are immunocompromised or hospitalized.